Acute gastric dilatation due to binge eating may be fatal - Oğuzhan Dinçel; Mustafa Göksu (İstanbul Kuzey Klinikleri, 2017)
Acute gastric dilatation was first described by Duplay in 1833. Since the stomach has rich blood circulation, necrosis and perforation due to dilatation are rarely seen. Clinically, more than 90% of cases have complaints of vomiting. The most useful method to determine diagnosis and etiology is computerized tomography (CT). Medical treatment is suitable for cases that have no necrosis or peritonitis findings. Delay in surgical treatment increases the risk of mortality. The present case is that of a diagnosis of gastric perforation due to acute gastric dilatation in a 24-year-old female patient.